Health Workers Motivation in the Implementation Early Initiation of Breastfeeding - Eka Nur Fitriana; Yuni Puji Widiastuti; Istioningsih Istioningsih (Global Health Science Group, 2020)
Early initiation of breastfeeding is the right of every baby. The obligation for health workers who provide assistance during labor is giving early initiate breastfeeding. However, not all babies are given an IMD and not all health workers do this. The causes are the lack of motivation of health workers in implementing early initiation of breastfeeding. The purpose of this study was to determine the motivation of health workers in implementation early initiation of breastfeeding at RSUD Dr. H. Soewondo Kendal. The research design used is quantitative with descriptive methods. The sample in this study amounted to 28 respondents with a total sampling technique. Instruments in the form of a questionnaire. Data analysis uses univariate. The results showed that the motivation of health workers in implementing Early Breastfeeding Initiation was in the